A Study on the Transmission of the Sampek Engtay Story from China and Its Adaptation in Indonesia - Wibowo, Atalya Mikhal Christsetyo (CV. Publikasi Indonesia, 2024)
The story of Sampek Engtay is one of the four famous Chinese folktales that have had a great influence in world literature. It spread to Indonesia and was successfully integrated into the local culture, where it became known as Sampek Engtay (山伯英台). The background of this research focuses on how Chinese immigrants played an important role in the spread and adaptation of this story in Indonesia, reflecting the longstanding cultural exchange between China and Indonesia. This research aims to explore the spread of Sampek Engtay in Indonesia by discussing the elements of the story's adaptation in Indonesia, using the novel *Sampek Engtay: A Feminine Liberation Romance by Oey Kim Tiang as an example. In addition, this paper also discusses the characteristics of OKT's adaptation of Sampek Engtay from the viewpoint of feminism and Chinese cultural imagery.The research method used is a qualitative method with a literature study approach, which involves analyzing cultural transmission and cultural adaptation. This analysis includes themes and narratives, characterizations, and differences and similarities in storytelling between the original and adapted versions. As such, this study provides an in-depth insight into how the Sampek Engtay story not only spread but also transformed in the Indonesian cultural context, highlighting the influence of Chinese immigrants and local cultural dynamics.